Effect of annealing using plasma-activated water on the structure and properties of wheat flour - Yan, Yizhe; Xue, Xinhuan; Jin, Xueyuan; Niu, Bin; Chen, Zhenzhen; Ji, Xiaolong; Shi, Miaomiao; He, Yuan (Frontiers in Nutrition, 2022)
In this study, wheat flour (WF) was modified by annealing (ANN) using plasma-activated water (PAW) for the first time. Compared with WF and DW-WF, the results of scanning electron microscopy and particle size analysis showed that the granule structure of wheat starch in PAW-WF was slightly damaged, and the particle size of PAW-WF was significantly reduced. The results of X-ray diffraction and Fourier transform infrared spectroscopy indicated that PAW-ANN could reduce the long-range and short-range order degree of wheat starch and change the secondary structure of the protein in WF, in which the content of random coils and α-helices was significantly increased. In addition, the analysis of solubility, viscosity and dynamic rheological properties showed that PAW-ANN improved the solubility and gel properties of WF, and decreased its viscosity properties and short-term regeneration. PAW-ANN, as a green modification technology, has the potential to be further application in WF modification and the production of flour products.